A Field-Wide Systematic Review and Meta-analysis of Putative Risk and Protective Factors for Radicalization Outcomes - Wolfowicz, Michael (Journal of quantitative criminology, 2020)
This systematic review sought to collate and synthesize the risk and protective factors for different outcomes of radicalization. We aimed to firstly quantify the effects of all factors for which rigorous empirical data exists, and secondly, to differentiate between factors related to radical attitudes, intention, and behaviors. The goal was to develop a rank-order of factors based on their pooled estimates in order to gain a better understanding of which factors may be most important, and the differential effects on the different outcomes.